Antibiotic Sensitivity Pattern of Bacterial Isolates in Patients with Chronic Rhinosinusitis in Kaduna, Nigeria - Musa, Emmanuel; Kodiya, Aliyu Mohammed; Kirfi, Abdullahi Musa; Nwaorgu, Onyekwere George B. (International Archives of Otorhinolaryngology, 2019)
Introduction A common practice in the management of patients with chronic rhinosinusitis (CRS), the empirical use of antibiotics may contribute to treatment failure and to the development of antimicrobial resistance.Objective To determine the antibiotic sensitivity pattern of aerobic and anaerobic bacteria associated with CRS.Methods This was a prospective cross-sectional study in which endoscopically guided middle meatal swabs (IBM Spss, version 16.0, Chicago, IL, USA) were aseptically taken from patients diagnosed with CRS after obtaining informed consent and ethical clearance. The samples were sent to the laboratory for qualitative and semiquantitative analysis via gram stain, aerobic, anaerobic cultures and antibacterial sensitivity tests. The collected data was analyzed using SPSS for Windows, version 16 (SPSS Inc, Chicago, IL, USA). Simple statistical parameters and paired sample t-test were used, as appropriate.Results There were 74 (56.92%) bacterial growths, out of which 55 (74.32%) were aerobic and 19 (25.68%) were anaerobic isolates, from a total of 130 patients. About 13 (17.5%–18%) of these bacterial growths yielded a mixed growth of aerobic and anaerobic isolates. The most common bacterial isolates were 26 (35.14%) Staphylococcus aureus, Haemophilus influenzae 9 (12.16%), Streptococcus viridians 8 (10.81%), and Streptococcus pneumoniae 5 (6.76%). Augmentin, ciprofloxacin, and Peflacine were found to be most effective, followed by levofloxacin, Rocephin, erythromycin and Zinat in that order.Conclusion Augmentin, ciprofloxacin and Peflacine have a sensitivity of 100%, while most of the organisms show resistance to Ampiclox, amoxicillin, and Septrin.
Keywords: antibacterial agent; amoxicillin-potassium clavulanate combination; bacteria; anaerobic; sinusitis